Por que os Projetos Alternativos à Fumicultura não vêm se Tornando Prioridade entre os Agricultores do Vale do Rio Pardo, Rio Grande do Sul? - Ronaldo Guedes de Lima (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2012)
This paper examines the question of the difficulties seen in the alternative projects to tobacco farming in the Vale do Rio Pardo, Rio Grande do Sul. It starts with the assumption that the production of tobacco in family units, interferes more intensively, braking the alternative projects productive diversification, whether the conventional base or the agroecological transition. The analysis seeks to discuss and reflect heavily on the raised question, but without ignoring that there are differing ideas or propositions about the meaning and practice of diversification in tobacco-producing areas. From completed empirical studies and the author's own experience in the region, it is concluded that the difficulties of promoting economic and productive alternatives to tobacco are not basically caused by the logistics of the tobacco industry, though, aspects of "economics" contained with this activity, as well as any other productive activities, are much more present in the attitudes / views of farmers. Farmers can remain in tobacco farming, for a basically material convenience, they can also quit or reduce the workload, while employed in projects alternative to tobacco growing, due mainly to the problem with the inconsistency of the market, among other obstacles found.